The Carbon Stock Potential of the Simpang Kapuak Village Forest as a Defense Against Climate Change in Lima Puluh Kota - Azzahara Adilani; Irma Leilani Eka Putri; Reki Kardiman; Dezi Handayani; Sandi Fransisco Pratama (PT Publikasiku Academic Solution, 2026)
The Nagari Simpang Kapuak Forest is one of the forests in West Sumatra with an area of 4,611.07 ha, of which it is not yet known how much carbon reserves are absorbed in this area. The purpose of this study is to determine the Flora Diversity and Carbon Reserve Potential in the Nagari Simpang Kapuak forest. This research was conducted using a field survey method. The level of vegetation taken in the forest is stakes, poles and trees with the research stage identifying the names of the types of vegetation of stakes, poles and trees, measuring the diameter at chest height (dbh). Calculation of carbon reserves using allometric equations. The results of the study showed that 17 species were found dominated by Syzygium chloranthum (Myrtaceae family). The total carbon stock in forest stand vegetation is 114,772.1449 tons C/ha., Pire-level vegetation has a total carbon reserve of 8,486.2687 tons/ha. The pole level is 25,506.9894 tons C/ha. Trees are 80,778.8867 tons/ha. Carbon stocks in the Nagari Simpang Kapuak Forest, Mungka District, Fifty Cities Regency are included in the high category according to Bappenas (National Development Planning Agency).